2018
DOI: 10.1111/luts.12243
|View full text |Cite
|
Sign up to set email alerts
|

A 52‐week multicenter randomized controlled study of the efficacy and safety of add‐on dutasteride and imidafenacin to tamsulosin in patients with benign prostatic hyperplasia with remaining overactive bladder symptoms (DIrecT study)

Abstract: Objective: The aim of this study was to examine the long-term efficacy of combination of tamsulosin 0.2 mg + dutasteride 0.5 mg + imidafenacin 0.2 mg (TDI) therapy compared with tamsulosin + dutasteride (TD) therapy for 52 weeks in benign prostatic hyperplasia (BPH) patients with a prostate volume (PV) ≥30 mL and remaining overactive bladder (OAB) symptoms after having received tamsulosin for ≥8 weeks. Previously, we reported that the improvement in OAB symptoms at 24 weeks was significantly greater in the TDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For the treatment of “LUTS/BPH” with large prostate (prostate volume >30 mL), the combination of an α‐blocker and a 5α‐reductase inhibitor (dutasteride) has been reported to be more effective, even in the storage symptoms, compared to each monotherapy 16,17 . However, the combination of α‐blocker, dutasteride, and anticholinergic drug has been reported to be more effective than the combination of α‐blocker plus dutasteride for the treatment of “BPH/OAB” with large prostate (DIrecT study) 18,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the treatment of “LUTS/BPH” with large prostate (prostate volume >30 mL), the combination of an α‐blocker and a 5α‐reductase inhibitor (dutasteride) has been reported to be more effective, even in the storage symptoms, compared to each monotherapy 16,17 . However, the combination of α‐blocker, dutasteride, and anticholinergic drug has been reported to be more effective than the combination of α‐blocker plus dutasteride for the treatment of “BPH/OAB” with large prostate (DIrecT study) 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, the combination of α-blocker, dutasteride, and anticholinergic drug has been reported to be more effective than the combination of α-blocker plus dutasteride for the treatment of "BPH/OAB" with large prostate (DIrecT study). 18,19 The purpose our study is to evaluate whether the combination of tadalafil and mirabegron is more effective than monotherapy with tadalafil in men with remaining OAB symptoms despite monotherapy with tadalafil. Thus, we recruited patients who had been taking tadalafil monotherapy but had remaining OAB symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high anticholinergic doses damage bladder contractility. Furthermore, compared with alpha-blocker monotherapy, add-on imidafenacin treatment showed better results in terms of improvements in OAB symptoms for BPH patients in a long-term evaluation [ 38 ]. Of course, much more research is needed to demonstrate the above points conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the DIrecT study, a 52-week multicenter, randomized, open-label, controlled trial, have been reported elsewhere [1,3]. In summary, patients with BPH (prostate volume ≥30 mL), aged ≤50 and <90 years, with OAB symptoms (total OABSS ≥3 and OABSS urgency subscore ≥2) after tamsulosin administration for ≥8 weeks were randomly assigned to the TDI group or the TD group at a 1:1 ratio and followed for 52 weeks.…”
Section: Methodsmentioning
confidence: 99%